Hybrid ship hulls engineering design rationales - Shkolnikov, Vladimir M. (Butterworth-Heinemann, 2014)
Hybrid Ship Hulls provides an overview of cutting-edge developments in hybrid composite-metal marine ship hulls, covering the critical differences in material processing and structural behavior that must be taken into account to maximise benefits and performance. Supporting the design of effective hybrid hulls through proper consideration of the benefits and challenges inherent to heterogenic structures, the book covers specific details of quality control, manufacturing, mechanical and thermal stress, and other behavioral aspects that need to be treated differently when engineering hybrid ship hulls. With a particular focus on heavy-duty naval applications, the book includes guidance on the selection of composite part configurations, innovative design solutions, novel hybrid joining techniques, and serviceability characterization